Biofortification of soybean sprouts with zinc and bioaccessibility of zinc in the sprouts. (15th April 2014) - Zou, Tao; Xu, Na; Hu, Guanglin; Pang, Jinwei; Xu, Hangdan
Abstract BACKGROUND Soybean sprouts are a very popular vegetable in Southeast Asian countries and regions. Zinc‐rich soybean sprouts can help to improve Zn deficiency in humans. The aim of this study was to prepare Zn‐enriched soybean sprouts through agronomic biofortification (germination with ZnSO4 solution) in order to provide consumers with a dietary material for Zn supplementation. RESULTS A suitable Zn concentration in ZnSO4 solution used for cultivation of Zn‐enriched soybean sprouts was found to be less than or equal to 20 µg mL−1. Upon biofortification with 10 and 20 µg Zn mL−1 ZnSO4 solutions, Zn content (102 and 163 vs 32 mg kg−1 dry weight (DW)), bioaccessible Zn content (3.86 and 8.53 vs 1.11 mg kg−1 DW) and Zn bioaccessibility (3.8 and 5.2 vs 3.5%) in edible portions of Zn‐enriched soybean sprouts were significantly enhanced compared with those of water‐germinated soybean sprouts. Meanwhile, no significant differences were observed in Fe, Mn and Cu contents of edible portions of soybean sprouts between ZnSO4 solution and water germinations, although soaking leakages of minerals (Fe, Mn and Cu) from soybean seeds to steeping media occurred to some degree. CONCLUSION Soybean sprouts biofortified with ZnSO4 solution at 10 or 20 µg Zn mL−1 contained appreciable quantities of Zn and had good Zn bioaccessibility, indicating that Zn‐enriched soybean sprouts may serve as a suitable dietary Zn source to improve the Zn intake of Zn‐deficient populations. © 2014 Society of Chemical Industry